Brief communication: Immunohistochemical detection of ACE2 in human salivary gland. Issue 2 (28th September 2020) - Usami, Yu; Hirose, Katsutoshi; Okumura, Masashi; Toyosawa, Satoru; Sakai, Takayoshi
Abstract: The novel, severe acute respiratory syndrome coronavirus (SARS‐CoV‐2) was firstly reported in late December of 2019 and subsequently caused a global outbreak. It has been shown that SARS‐CoV‐2 uses ACE2 (Angiotensin Converting Enzyme 2) as a cellular receptor for host cell entry through the surface unit of SARS‐CoV spike glycoprotein. In this brief report, we analyze ACE2 protein expression and localization in human salivary gland, and propose a possible role of saliva in the pathogenesis of Coronavirus disease 2019 (COVID‐19).